PEMBERANTASAN TINDAK PIDANA KORUPSI MELALUI UPAYA PENAL DAN NON-PENAL DI INDONESIA (DALAM PERSPEKTIF CRIMINAL POLICY) - Riski Amelia; Saut P. Panjaitan; Henny Yuningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Crime is something that cannot be avoided. One form of crime that often occurs is premeditated murder. Premeditated murder cases are triggered by several factors. In this case the author will examine the factors that cause a person to commit a criminal act of premeditated murder in the study of Criminology and theories in criminology which can be used as a basis for analyzing the motive for a premeditated murder. This research uses qualitative methods by describing data sources, books and existing literature. From the results of research carried out by the author, in crime cases, especially cases of premeditated murder which the author addresses in this article, Criminology examines the factors that cause a person to commit the crime of premeditated murder, namely: Economic Factors, Revenge Factors, Environmental Factors, and Educational Factors that is often the reason or cause in a case of premeditated murder. The criminological theories used in analyzing a motive for premeditated murder are: Differential Association Theory, Anomie Theory, and Social Control Theory.